Experimental evaluation of a power management system for a hybrid renewable energy system with hydrogen production. (December 2017) - Higuita Cano, Mauricio; Agbossou, Kodjo; Kelouwani, Sousso; Dubé, Yves
Abstract: This study presents a power management system (PMS) for a hybrid renewable-energy system (HRES) using hydrogen as an energy vector. The PMS is based on a fuzzy control system takes into account the uncertainties of the load demand and the power production from renewable energy sources (RES). The fuzzy control system evaluated differs of the traditional PMSs, as it considers a single-level prediction of the DC net power and its uncertainty from of HRES allowing a suitable decision that increases the lifetime of the fuel cell-electrolyzer and boosts the hydrogen production. The robustness of the proposed PMS is evaluated in simulation through a stochastic analysis using the Monte Carlo method (MCM). The probabilistic analysis provided better results for the HRES and its control system. Finally, the fuzzy logic controller (FLC) is tested experimentally applying the Hardware-in-the-Loop (HIL) technique on an HRES test bench. The experimental results are satisfactory, and the response of the control system is as expected. Highlights: The experimental validation of PMS based on uncertainty by applying the Hardware-in-the-Loop (HIL) technique on an HRES test bench. To evaluate the robustness of the PMS through a stochastic analysis using a Monte Carlo simulation. To explore the different intermittent conditions of the RES that the HRES and its PMS must face.